Towards Green Economy by Strengthening Supervision of Business Activities - Huristak Hartawan Hasibuan, Ali; Arifin, Zainal; Nur Dwi Ulvana, Adella (Journal of Private and Commercial Law, 2023)
This Paper underscores the fundamental right of individuals to live in a healthy environment, as guaranteed by the 1945 Constitution of Indonesia. Highlights the growing global environmental challenges, including species extinction, climate change, and pollution, specifically focusing on the Indonesian context. Attention to the intricate relationship between economic activities and environmental degradation, advocating for a shift towards environmentally friendly practices. Employs a normative juridical methodology to analyze the existing legal framework related to environmental monitoring in Indonesia. Scrutinizes the state's environmental control responsibilities and emphasizes the need for enhanced environmental supervision. In the results and discussions section, the Paper explores the state's responsibilities in environmental control, underscores the importance of administrative and criminal sanctions in environmental oversight, and advocates for stringent penalties to discourage non-compliance. The study's findings aim to contribute to the ongoing discourse on environmental protection and sustainable development, emphasizing the urgency of proactive measures to address environmental challenges and promote Indonesia's healthier and more sustainable future.